Técnicas de narración para desarrollar la expresión oral en los niños de primer año de educación básica Chimborazo de la Unidad Educativa san Felipe Neri de la cuidad de Riobamba durante el periodo de febrero –julio 2018. - Naranjo Mayacela, Lizeth Priscila (2018)
The investigation narrative techniques to develop the oral expression in the children of first grade from basic education Chimborazo of Unidad Educativa San Felipe Neri of the city of Riobamba during the period of March -June 2018, was elaborated with the objective of developing oral expression through storytelling techniques in children from 5 to 6 years old. It is based on the concept of philosophy and the pedagogy of Maria Montessori. The theoretical foundation is constructed based on the study variables, with the following topics oral expression, narrative techniques. The research is of quasi-experimental design, of applied type, of laboratory and bibliographic, the method used for the fulfillment of the analysis and interpretation of results the deductive method. We worked with 25 children from the Unidad Educativa San Felipe Neri in the city of Riobamba. For the solution of the problem the guide narrative technical activities is proposed to develop the oral expression. Once the guide is applied and the observation card is used, the results are analyzed and interpreted. Using the Chi square, the specific hypotheses are checked. It is concluded that technical narrative activities to develop oral expression is a success, since with the proposed techniques, diction, emotion, message comprehension, fluency, clarity and vocabulary have been developed in children from 5 to 6 years of age of basic education of the Unidad Educativa San Felipe Neri of the city of Riobamba.